2018
DOI: 10.1177/1556264617751475
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Factors Associated With Honorary Authorship in Indian Biomedical Journals: Analysis of Papers Published From 2012 to 2013

Abstract: Honorary authorship is the inclusion of an author on an article whose contribution does not warrant authorship. We conducted an Internet-based survey among first authors publishing in Indian biomedical journals from 2012 to 2013 to study the frequency and factors associated with honorary authorship. The response rate was 27% (245/908) with the prevalence of perceived, International Committee of Medical Journal Editors (ICMJE)-defined, and unperceived honorary authorship of 20.9% (50/239), 60% (147/245), and 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…We found that most researchers in South Africa (in all fields of study) were familiar with authorship guidelines (850; 87.9%). This is somewhat lower than the finding of Nylenna and colleagues (634; 97%) regarding Norwegian researchers in the medical sciences at the University of Oslo (Nylenna et al, 2014) but it compares favorably with the findings of Alshogran and Al-Delaimy (2018) that 74 (27.2%) of their respondents in Jordan and Shah et al (2018) that 126 (26%) of their respondents in India were aware of the presence of the ICMJE guidelines. However, it should be noted that our study included respondents in all fields of studies, and not only in medicine and health sciences and our use of the term guidelines in the questionnaire was used generically; we did not specify any particular guideline.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We found that most researchers in South Africa (in all fields of study) were familiar with authorship guidelines (850; 87.9%). This is somewhat lower than the finding of Nylenna and colleagues (634; 97%) regarding Norwegian researchers in the medical sciences at the University of Oslo (Nylenna et al, 2014) but it compares favorably with the findings of Alshogran and Al-Delaimy (2018) that 74 (27.2%) of their respondents in Jordan and Shah et al (2018) that 126 (26%) of their respondents in India were aware of the presence of the ICMJE guidelines. However, it should be noted that our study included respondents in all fields of studies, and not only in medicine and health sciences and our use of the term guidelines in the questionnaire was used generically; we did not specify any particular guideline.…”
Section: Discussioncontrasting
confidence: 66%
“…A systematic review of 123 articles describing empirical quantitative or qualitative research from all scholarly fields on different aspects of authorship demonstrated that authorship issues were more frequently (55% vs. 23%) reported by researchers outside of the United Kingdom/United States (i.e., France, South Africa, India, and Bangladesh) when compared with researchers in the United Kingdom/United States (Marušić, Bošnjak, & Jerončić, 2011). Surveys of researchers' awareness of authorship criteria and of trends in authorship practices in Jordan (Alshogran & Al-Delaimy, 2018) and India (Shah, Rajasekaran, Bhat, & Solomon, 2018) confirm a lower level of awareness of authorship criteria and a higher prevalence of questionable authorship practices in those parts of the world. A South African study exploring authorship practices and experiences related to articles published in the Faculty of Health Sciences at the University of the Free State found that in only 9% of the articles all the listed authors met all the three criteria for authorship stipulated in the International Committee of Medical Journal Editors (ICMJE [2018]) guidelines (Joubert, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey conducted in 2008, directed at corresponding authors of articles published in six top medical journals, the reported prevalence of nondeserving authors was 21%, a decrease from 29% in a similar survey conducted in 1996; in reports of original research, the stated prevalence of honorary authors was 25%, while it was considerably lower in reviews and editorials (Wislar et al, 2011). In a recent article published in this journal, investigating responses from scientific authors who had published in Indian biomedical journals, slightly over 25% of the respondents stated that the senior member of the department was automatically listed as an author on articles from the department, regardless of his or her contribution, and 60% claimed to have included nondeserving persons as authors (Shah, Rajasekaran, Bhat, & Solomon, 2018). In a article documenting low-/middle-income country health researchers’ experiences and views, 77% reported that nondeserving authors were included on articles at their institution (Rohwer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Adeleye and Adebamowo (2012) found that in Nigeria there is a significant degree of fabrication, falsification, and plagiarism in academic publications, and they argue that a lack of knowledge of research ethics coupled with pressure to publish enough papers for promotion were at the heart of this phenomenon. Shah et al (2018) reported increased incidents in India of "honorary authorship" among academics, that is, the inclusion of an author on an article whose contribution to the article did not warrant authorship (2018,187). In South Africa, it has been found that the majority of academics find it difficult to apply authorship criteria and there are high levels of disagreement concerning who should be included as a co-author and in which order (Breet et al 2018).…”
Section: Pressure To Publish In the International Contextmentioning
confidence: 99%